A New Current-Based Technique for Discrimination between Internal Faults and Inrush Current within Power Transformers - El-Naggar, M.; Abu-Siada, Ahmed; Mahmoud, A.; El Mola, K. (CRC Press, 2015)
Inrush current may lead to a false operation of the power transformer differential protection relay. Hence, it is very essential to distinguish inrush current from various internal transformer faults in order to improve the reliability of the differential protection scheme. This paper presents a new current-based technique to discriminate transformer inrush current from transformer internal faults. The proposed technique relies on converting the three phase transformer currents in both sides into modal current components using Clarke's transformation to produce three current modes namely, ground mode, areal mode 1 and areal mode 2. The features extracted from the three modes are then applied to the inrush discrimination equation proposed in this paper. The robustness of the proposed technique is evaluated through extensive simulation studies on a 132/15 kV, 155MVA power transformer using electromagnetic transient program (EMTP-ATP). Simulation results show the effectiveness of the new proposed technique in discriminating magnetizing inrush current from other transformer internal faults.